Can Geographical Indications Modernize Indonesian and Vietnamese Agriculture? Analyzing the Role of National and Local Governments and Producers' Strategies. (October 2017) - Durand, Claire; Fournier, Stéphane
Highlights: An analysis of legal frameworks and four case studies shows the State role in GI. GIs are a development tool whose uses vary with the local context. GIs can be used as a tool for agricultural modernization. Local government involvement facilitates negotiation on GI orientation. Summary: This paper investigates the way Geographical Indications (GIs) are implemented by national and local governments in Indonesia and Vietnam. The two States are active at all stages of GI development, from the selection of the products candidates for GI registration to the supervision of the GI implementation. Thanks to the involvement of national experts from public agencies in the establishment of the Codes of Practices (CoP), they are able to push for the substitution of traditional local techniques with "good practices" (i.e., mostly those recommended by research centers worldwide). Thus, they put GIs at the service of agricultural modernization when GIs apply more conventionally to specific products based on traditional know-how. However, the implementation of the CoPs and thus the achievement of this objective of modernization depend on the perceived interest of producers in the whole GI dynamic. Indeed, the cases studied in Indonesia and Vietnam highlight the variable level of participation of local producers in the GI. In the four studied cases, the CoPs are mainly based on expert knowledge which differs from the actual practices of farmers and processors. Moreover, GIs are implemented in order to create or reinforce reputations rather than legally protecting preexisting ones. For these two reasons, producers' motivation to invest in GI certification is weak, which makes difficult the necessary collective involvement. In both countries, the involvement of local governments in GI construction and management modifies the situation. Thanks to their knowledge of local situations and stakes, they are more likely than national experts to identify the most strategic supply chains at local level, enable participatory approaches in GI construction and facilitate the involvement of local producers in the GI managing group. But if competences have been given to local governments in the Indonesian and Vietnamese legal frameworks, the distribution of roles between central and provincial governments in GIs are not clearly enough specified. The nature and the importance of local public intervention differ from one case to another. Finally, this paper recognizes the legitimacy of State intervention in GI development, at least as long as producers' awareness of GIs is still low. However, this State intervention should not only let enough space for producers in GI governance, but also design a frame for arousing their interest and adhesion and for facilitating their collective involvement. That may be facilitated by a concrete and clearly established decentralization of competences in national policies.